Repair of Breast Defect by Transfer of a Contralateral Internal Mammary Artery Perforator Flap. Issue 1 (January 2022) - Yang, Qingfeng; Wu, Zankai; Zhang, Xue; Feng, Juan; Zhao, Hengqiang; Liao, Lingxia; Cui, Le; Gong, Yiping
Abstract : Summary: This is a case report of a patient with a borderline phyllodes tumor in the left breast. Seventeen months after the resection of the phyllodes tumor from the patient's left breast, the tumor occurred again 5 months ago in the surgical region. A large defect was generated after the extended resection of the left breast mass, and it was repaired with a contralateral internal mammary artery perforator flap. After the operation, bilateral breast symmetry was good, and the patient was satisfied with the shape of the breast. Postoperative follow-up was performed for 15 months, and no local recurrence was observed.